IMPLEMENTASI AKAD QARDH TERHADAP PEMBIAYAAN DI KOPERASI AMANAH MULIA IKHLAS (KAMI) KABUPATEN PINRANG - Aisyah Ramadhani; Mustamin B; Andi Bisyriani (STAI DDI Pinrang, 2024)
The qardh contract financing procedure at the Amanah Mulia Ikhlas Cooperative in Pinrang Regency is a process of providing loans without interest that is mutually beneficial between members. Customers or members submit financing applications to the cooperative by completing administrative requirements. After going through a verification process and feasibility analysis, the cooperative will disburse the loan funds. Customers are then required to repay the loan within the agreed time period, without additional interest. The entire process follows sharia principles, avoids usury, and prioritizes the principles of justice and mutual benefit. The implementation of the qardh contract in financing at the Amanah Mulia Ikhlas Cooperative in Pinrang Regency has been truly implemented.